Norton anthology of western music (W.W. Norton, 2006)
This comprehensive collection of scores illustrates every significant trend and genre of Western music from antiquity to modern times, with a strengthened emphasis on twentieth-century music. The ideal companion to A History of Western Music, Seventh Edition, the Norton Anthology of Western Music, Fifth Edition, includes 172 historically significant scores, 71 of them new to this edition, with a strengthened emphasis on twentieth-century music.